PENERAPAN MANAJEMEN RISIKO DI UNIT KERJA RMIK: STUDI KASUS PADA TEMPAT PENDAFTARAN PASIEN RAWAT JALAN (TPPRJ) RUMAH SAKIT - Zefan Adiputra Golo; Arief Azhari Ilyas; Isnaini Qoriatul Fadhilah; Sugiharto (JRMIK, 2023)
Background: TPPRJ as a leading unit that provides services to patients needs to minimize the risks and hazard that can be experienced by officers and patients. From a preliminary study at one of the local government hospitals in the Central Java region, it was found that at the outpatient registration point there was no Standar Procedur Operational (SPO) regarding risk management, so there was no standard set for risk control for officers and patients.Objective: The purpose of this study is to identify the application of risk management in the outpatient registration site (TPPRJ) of the hospital.Method: The type of research used in this study is qualitative descriptive with a case study design. The subjects of the study were 4 informants determined by purposive sampling techniques. Data collection through interviews and observationsResults: There are several risk factors in TPPRJ, namely from physical aspects (air temperature, lighting, radiation), biological aspects and ergonomic aspects. From the results of interviews and observations, it is known that the implementation of risk management in hospitals has been running, but it is still not optimal because it has not yet reached a comprehensive evaluation from the hospital's quality management.Conclusion: Risk management has been running but has not been maximized, because there is no SPO that specifically regulates risk management at TPPRJ. The risk management process that has been running is to identify risks, risk analysis and risk control.Keywords: Risk Management, RMIK Work Unit, TPPRJ